SERBIAN TERMS FOR PROPERTY 1804–1918 - Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The subject of the article are Serbian terms for ‘property’ used between 1804 and 1918. The author put forward the words with the meaning ‘property’, exposed some of the sources in which these terms could be found and tried to determine their etymology. The paper also sheds light on the terms meaning ‘coproperty’. The words denoting ‘property’ were following: baština, vlasništvo, vlas(t)nost, vlast, vlastbina/vlazbina, vlastitost/vlastitošt, vlastitstvo/vlaštitstvo, vlaština, gospodarstvo/gosudarstvo, imanje, imaostvo, imovina, pritjažanije/pritežanije, pritjažavanje, svojina and sobstvenost/sopstvenost. In the texts dating from aforementioned period, 'coproperty' can be found under following terms – susvojina, suvlas(t)nost, suvlaština, sogospodarsvo, sasobstvenost, sogospodarstvo, imaostvo and smesništvo. Such large number of words prove a great degree of roaming in building Serbian terms for 'property' and 'coproperty'. Moreover, some of the terms have dublets being the result of parallel existence of three types of literary language among the Serbs (Church Slavonic of Russian recension and Slavonic-Serbian) and dialectal varieties, which brought about even greater diversity of the terminology for 'property'. Serbian words prevail among the terms. Some of them were derived from an other Serbian word, as the other are calques. Root words of the derivatives are mostly noun vlast ('power, authority') and verb imati ('to have'), the terms semantically expressing the meaning of property the best. In some cases the words for 'property' were forged by broadening or narrowing the genuine meaning of a certain word (for instance, sobstvenost, the word coming from Russian recension of Church Slavonic, originally meant 'the thing belonging to somebody' and thence became 'property'). The calques were formed on either German or Latin words, which is understandable, taking into consideration that Serbian educated lawyers, forgers of the terms, originated from Habsburg Monarchy. The quality of some calques might be considered debateable, neverthess the efforts to make Serbian terms instead of borrowing foreign words are praiseworthy. Loan words for 'property' had come to Serbian from Russian recension of Church Slavonic and were constantly getting more Serbian shape as the time progressed, which was the general tendency in Serbian language at that time.